Different Exegesis of the Concepts Related to Mixed Transport - Kurenkov, Petr; Astafiev, Alexey; Kaplina, Olga (Communications - Scientific letters of the University of Zilina, 2016)
This article contains a short history of existing types of mixed transport in Russia and abroad. The system of export freight delivery is analyzed in association with all forms of interaction between various modes of transportation and the subjects of the transport service market (TSM). There is focus not only on the transport complex organization departments and management levels of various modes of transportation, but also on other TSM subjects (carriers, cargo owners, forwarders, stevedores, marine agents, banks, organizations responsible for expertise, customs control and document completion, etc.).